Three Essays on Organizational Socialization from Dissimilar Employee’s Perspective - (:unkn) unknown (My University, 2020)
This dissertation consists of 3 essays all of which seek to examine the socialization experiences of newcomers who perceive themselves to be dissimilar from their work colleagues before, during, and after they start their jobs. I define the perceived dissimilarity as the degree to which individuals perceived themselves to be different from most others in the organization. The first essay provides a comprehensive review of the theoretical and empirical literature on organizational socialization, identifies four dominant theoretical perspectives and their gaps, and sets the stage for the research model developed for this dissertation. At the end of the first essay, the integrative model of organizational socialization is introduced, which incorporates important elements of the four influential research perspectives to examine the socialization processes and outcomes of newcomers who perceive themselves to be dissimilar to their work colleagues during the anticipatory stage (pre-organizational entry), accommodation stage (immediately following organizational entry), and role management stages (six months after starting new work role). The second essay focuses on understanding the anticipatory (pre-organizational entry) stage of dissimilar newcomers’ socialization experiences. Specifically, it examines the interaction between individual and contextual factors on proactive socialization behaviors of newcomers’ who perceive themselves to be dissimilar from their work colleagues. The third essay focuses on understanding the socialization experiences of newcomers’ who perceive themselves to be dissimilar from their work colleagues during the last two stages of the organizational socialization process (accommodation and role management stage). Specifically, it examines the interaction between individual and contextual factors on newcomers' proactive socialization behaviors and adjustment and attitudinal outcomes one month and six months after starting their new work role. Data is collected at 4 times (pre-entry, 2 weeks after entry, 3 months after entry, 6 months after entry) by collaborating with Qualtrics data collection team. The final sample size consists of 80 people who had an offer but had not started working at time 1. The theoretical and practical implications of my research are discussed at the end of the essays.
Keywords: cultural intelligence; dissimilar newcomer; integrative model; organizational socialization; perceived diversity climate; proactive socialization